Business Solution for Low Utilization of CVC Station in Heavy Oil Operations PT Chevron Pacific Indonesia - Eko Nugroho, Andy; Hasan Basri, Mursyid (The Indonesian Journal of Business Administration, 2016)
Abstract. In current situational, oil and condensate still valuable in market even though price was fluctuates and tend to decrease. Oil companies project push initiatives to run effectively and efficiently, especially for cost spending. Moreover for PTCPI in Indonesia, has end of contract in 2021, which make management hurdle to spend more cost for long time project and economically promising.Production 1 Team Duri Field has 8 Casing Vapor Collection (CVC) stations to separate and vapors condense of receiving fluids from casing of production wells. 18,000 bfpd average of vessel capacity provided are enough to handle production as forecasted. But actually it is only 6% of total vessel capacity where fill up the fluid supply. It means that low utilization of facility was occurred. After doing Root Cause Analysis (RCA) using why tree method, all factor affected in facility utilization are proper condition include cost reduction.  Each of the attributes need to cross-linked with variable of impact criteria as company requirement to get the best alternative chosen as strategy to be applied.  Comprehensive analysis of CVC station based on capacity utilization rate current and future, forecast of total fluids processing, and room space capacity itself processing system are needed for utilization existing station without sacrifice the production. Based on focus group discussion for several selected alternatives, taking one or more CVC station to consolidate processing facilities is chosen.  7 of 16 best consolidation alternatives of station were chosen using decision driver. After comparing each capacity utilization rate and no processing station duplication, multiple processes were generated by using interconnection lines with 2 CVC and FFC station still kept to be operated. Other stations need to be shut down and proposed to demolish after getting approval from SKKMigas. This business solution will be implemented during 20 weeks since initialing proposal strategy, sequential for execute the scenario, and it has potentially to increase 33 – 83% vessel capacity and give 64% cost spend reduction. Keyword: vessel capacity, utilization, interconnection lines, cost spend reduction